2021
DOI: 10.1681/asn.2020111665
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Kidney Outcomes Following Dialysis-Treated Childhood Acute Kidney Injury: A Population-Based Cohort Study

Abstract: Background Acute kidney injury (AKI) is common during pediatric hospitalizations and associated with adverse short-term outcomes. However, long-term outcomes among survivors of pediatric AKI who received dialysis remain uncertain. Methods To determine the long-term risk of kidney failure (defined as receipt of chronic dialysis or kidney transplant) or death over a 22-year period for pediatric survivors of dialysistreated AKI, we used province-wide health administrative databases to perform a retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 66 publications
5
30
0
Order By: Relevance
“…We found that a further progression of renal injury after AKI could add the risk of 30- and 90-day adverse outcomes, which supported the results of our previous study of AKD in hospitalized adult patients with AKI ( 8 ). AKI stage 2–3, which was generally considered to be associated with increased risks of CKD, kidney failure, and mortality ( 1 , 16 18 ), was no longer a predictor for adverse outcomes in our multivariable logistic regression analysis. However, AKD stage 2–3 became the strongest predictor of MAKE30 with odds ratio being 12.18 (95%CI, 7.38–20.09) and still carried a 2.49–fold increased risk of adverse 90 days outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…We found that a further progression of renal injury after AKI could add the risk of 30- and 90-day adverse outcomes, which supported the results of our previous study of AKD in hospitalized adult patients with AKI ( 8 ). AKI stage 2–3, which was generally considered to be associated with increased risks of CKD, kidney failure, and mortality ( 1 , 16 18 ), was no longer a predictor for adverse outcomes in our multivariable logistic regression analysis. However, AKD stage 2–3 became the strongest predictor of MAKE30 with odds ratio being 12.18 (95%CI, 7.38–20.09) and still carried a 2.49–fold increased risk of adverse 90 days outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…The pediatric acute kidney injury (AKI) research field has expanded during the past decade with international epidemiologic studies, long-term AKI follow-up studies, validation of AKI prediction models, and continued investigation of novel AKI biomarkers. [1][2][3][4][5][6][7][8][9] The 26th Acute Disease Quality Initiative (ADQI XXVI) convened in Napa, California, in November 2021, the first Pediatric ADQI (pADQI) that specifically addressed the global burden of AKI in the child and young adult population, with focused attention paid to kidney development and AKI, prenatal or neonatal kidney physiology, dialysis devices engineered for children, 10 and the unique aspects of pediatric AKI epidemiology. The pADQI was assembled to mirror the global workforce in pediatrics and used a public and patientfacing approach.…”
Section: Introductionmentioning
confidence: 99%
“…One of our studies revealed that serum neutrophil gelatinase-associated lipocalin could be used as a predictor for successful RRT discontinuation in patients with nonseptic AKI, rather than in those with septic AKI 3 . In the study by Robinson et al , 1 it might be similarly speculated that pediatric survivors of cardiac surgery–associated AKI and other types of AKI had different clinical trajectories in later life, thus necessitating risk stratification and adaptive follow-up surveillance.…”
mentioning
confidence: 87%
“…We read with great interest “Long-term kidney outcomes following childhood acute kidney injury receiving dialysis: A population-based cohort study” by Robinson et al 1 . In this retrospective cohort study, 1699 pediatric survivors of dialysis-treated AKI were followed up for a median of 9.6 years to evaluate long-term kidney outcomes.…”
mentioning
confidence: 99%